Investigation of the spatial and energy distributions of neutrons in the massive uranium target irradiated by deuterons with energy of 1…8 GeV - Artiushenko, M.Yu.; Voronko, V.A.; Husak, K.V.; Kadykov, M.G.; Petrusenko, Yu.T.; Sotnikov, V.V.; Irzhevskyi, D.A.; Tyutyunnikov, S.I.; Furman, W.I.; Chilap, V.V. (Вопросы атомной науки и техники, 2013)
The paper presents the results of investigations of nuclear-physical characteristics of neutron fields generated in a massive uranium target irradiated by deuterons with an energy of 1, 4, 8 GeV. The research was performed within the framework of the scientific program "Research of the deeply subcritical accelerator-driven systems and possibilities of their use for energy production and transmutation of radioactive waste" project “Energy and Transmuta-tion RAW”, JINR, Dubna, Russia